Dosis Pemberian Gonadotropin Releasing Hormone Yang Berbeda Dengan Pgf2α Terhadap Karakteristik Estrus Dan Keberhasilan Inseminasi Buatan Domba Ekor Tipis Betina - Priyatun, Rumi; Wibowo, Haris Tri; Andanawari, Suci; Akbarrizki, Muzizat; Rosa Zulfikhar; Wahyuni, Sri; Siswanto, Ferbian Milas; Cahyani, Annisa Putri (Jurnal Sain Peternakan Indonesia, 2025)
Estrus synchronization is one method to standardize the estrus cycle in thin-tailed sheep. The objective of this study was to evaluate estrus quality and the success of artificial insemination using PGF2α hormone combined with GnRH. Hormones were administered by intramuscular (IM) injection. Sixteen female thin-tailed sheep aged 2–3 years with body weights of 33–35 kg were used. Treatments were divided into four groups with four replications: P0 (PGF2α 1 ml + GnRH 0 ml), P1 (PGF2α 1 ml + GnRH 0.5 ml), P2 (PGF2α 1 ml + GnRH 1 ml), and P3 (PGF2α 1 ml + GnRH 1.5 ml). Estrus observation was conducted visually. Artificial insemination was performed using frozen semen, and pregnancy detection was carried out with the PregnaDrop test kit. Data were analyzed using descriptive statistics and the Kruskal–Wallis test. The results showed that the administration of GnRH and PGF2α significantly affected the success of artificial insemination, with estrus onset differing significantly (P<0.05) and estrus intensity differing highly significantly (P<0.05). The best dose was found in P3 (PGF2α 1 ml + GnRH 1.5 ml).